Whatever happened to the Egyptians? : changes in Egyptian society from 1950 to the present - Amin, Galal A., 1935-2018 (American University in Cairo Press, 2000)
Based on both academic research and the author's own personal experiences and impressions, this delightful and informative book examines the underlying causes of some of the more disturbing social, political, economic, and cultural phenomena that characterize Egyptian society in the 1990s. Egypt's crisis of culture and other woes are often attributed to the 'open door policy' (Infitah) initiated under President Sadat in the mid-1970s, and to the large-scale migration of Egyptian workers to the oil-rich states of the Gulf that began around the same time. Galal Amin contends, however, that these.